Lexical Errors in English Students' Writing - Afrillia Anggreni; Siska Bochari (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2021)
This research analyzed lexical erros in writing of English students and focused on three types of errors; they were errors in literal translation, errors of word formation, and errors in word choice. This research aimed to explore the most frequent errors and the factors of errors made by English students. The design of this research was qualitative in which the data were colleted by using document in the form of students’ writings and interview. The informants of the research were thirty students majoring in English study program at Tadulako University. The result of this research showed that the most frequent errors made were in word choice and followed by errors in literal translation and errors in word formation. The factors causing the errors were students’ inability to consider the context of the topics when writing. They only focused on using dictionary, Google translate, or simply the words that they had in mind to express ideas in their writing. The students also never used words that were related to the topic in their daily interaction.